Principles of Marketing - Philip Kotler; Gary M. Armstrong; Lloyd C Harris; Hongwei He (Hoboken, NJ Pearson Education Limited, 2020)
Revised edition of the authors' Principles of marketing.
Keywords: Marketing; Textbooks; Business; (MGT-103) Understanding Markets and Marketing